THE INFLUENCE OF EDUCATION AND TRAINING ON THE PERFORMANCE OF CIVIL SERVANTS IN THE PERSONNEL AND HUMAN RESOURCE DEVELOPMENT AGENCY OF PASER DISTRICT - Dedy Darmawan; Achmad Syahruddin; Nuriyah Nuriyah; Sofya Ariska (Jurnal Mahasiswa Manajemen, 2025)
This study aims to determine the effect of education and training (X) on the performance of civil servants (Y) at the Human Resources Development and Personnel Agency of Paser Regency, with a sample of 36 respondents using a saturated sampling technique. The research instrument in the form of a questionnaire was tested for validity and reliability, where all 10 statement items were declared valid (tcount > ttable 0.3291) and reliable with a Cronbach’s Alpha value of 0.851 > 0.60, thus categorized as good. The simple linear regression analysis produced the equation Y = 1.082 + 0.755X with a correlation coefficient of 0.681, indicating a strong relationship between education and training and employee performance. The R Square value of 0.463 shows that the education and training variable contributed 46.3% to the improvement of employee performance, while the remaining 53.7% was influenced by other factors outside this study. The t-test results indicate a significant effect of education and training on employee performance with tcount 5.417 > ttable 2.03224, meaning that the hypothesis is accepted. Thus, it can be concluded that education and training play an important role in improving the performance of civil servants at the Human Resources Development and Personnel Agency of Paser Regency, and therefore need to be a primary concern in human resource development within the institution.